(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines one of the key elements of the theoretical basis of linguistics, discusses questions about the hypothesis of linguistic relativity, provides information about the authors of this hypothesis, Edward Sapir and Benjamin Lee Whorf. The purpose of the article is to analyze the results of linguistic experiments and the influence exerted by the Sapir-Whorf hypothesis (SWH) on the development of linguistics.